A Novel Model of Perifascial Areolar Tissue Transplant in Rats - Oshima, Junya; Sasaki, Kaoru; Shibuya, Yoichiro; Sekido, Mitsuru (Indian Journal of Plastic Surgery, 2022)
Background Perifascial areolar tissue (PAT) transplant is a method of transplanting loose connective tissue harvested in a sheet form from above the fascia to the wound bed and is effective for wounds with exposed ischemic tissue. However, the engraftment mechanism is unknown, and no animal models of PAT transplant for wound healing exist.Methods In this study, we harvested connective tissue from the backs of Wistar rats in a sheet form to simulate a human PAT transplant. The PAT was affixed to exposed bone of the head.Results In the PAT(+) group, the wound areas gradually decreased due to epithelialization and contraction. The wound area of the PAT(+) group was significantly smaller than that of the PAT(−) group.Conclusions This clinically relevant rat model is useful for elucidating the mechanism of the PAT transplant and establishing a reliable surgical method.
Keywords: perifascial areolar tissue; loose connective tissue; model; grafts; bone exposure